Electron-plasmon model in the electron liquid theory - Vavrukh, M.V.; Slobodyan, S.B. (Condensed Matter Physics, 2005)
Here we propose an accurate approach to the description of the electron liquid model in the electron and plasmon terms. Our ideas in the present paper are close to the conception of the collective variables which was developed in the papers of Bohm and Pines. However we use another body of mathematics in the transition to the expanded space of variable particles and plasmons realized by the transition operator. It is evident that in the Random Phase Approximation (RPA), the model which consists of two interactive subsystems of electrons and plasmons is equivalent to the electron liquid model with Coulomb interaction.